2018
DOI: 10.7567/apex.11.102501
|View full text |Cite
|
Sign up to set email alerts
|

Coherent mid-infrared supercontinuum spectrum using a step-index tellurite fiber with all-normal dispersion

Abstract: We demonstrate a coherent mid-infrared supercontinuum generation in a step-index tellurite fiber with an all-normal dispersion profile. A coherent supercontinuum spectrum spanning 1340–2840 nm in a 6.3-cm-long tellurite step-index fiber is obtained when the fiber is pumped with 200 fs laser pulses with a coupled peak power of 5.5 kW at 2000 nm. Such fiber-based coherent mid-infrared supercontinuum sources are highly required for the imaging of biological tissues in optical coherence tomography, pump–probe spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The transmission range of the ZnSe lens was 0.6-21.0 µm. The signal received from the monochromator was amplified using a lock-in-amplifier (NF LI5640) [34][35][36] . Finally, the supercontinuum spectrum was recorded using a computer based spectrometer system.…”
Section: Fiber Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmission range of the ZnSe lens was 0.6-21.0 µm. The signal received from the monochromator was amplified using a lock-in-amplifier (NF LI5640) [34][35][36] . Finally, the supercontinuum spectrum was recorded using a computer based spectrometer system.…”
Section: Fiber Fabricationmentioning
confidence: 99%
“…The optical noise generated by the nonlinear processes (such as modulation instability and the soliton fission) is completely absent in the case of ANDi engineered fibers pumped with femtosecond laser pulses 26 33 . Our group has demonstrated coherent mid-IR supercontinuum generation in step-index tellurite, tapered tellurite, and chalcogenide double clad optical fibers pumped with femtosecond laser system [34][35][36] . Among all the fibers, the chalcogenide glass fibers are much suitable candidate for mid-IR supercontinuum applications.…”
mentioning
confidence: 99%
“…In general, the exploitation of compact and robust fiber SC schemes with improved coherence and flatness could be advantageous for applications like absorption spectroscopy or pulse recompression [17][18], but still requires considerable efforts beyond 2 µm to reach the remarkable efficiency already demonstrated in the near-IR. To this regard, several experimental attempts have been already reported in the important spectral transition between near-IR and mid-IR (1.5-3.5 μm) [13,[19][20][21][22][23][24] by using normal dispersion fibers made of chalcogenide or tellurite glasses. Note that only Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Petersen et al demonstrated mid-infrared SC generation in a large-mode-area chalcogenide PCF taper [16]. In 2018, Saini et al investigated the coherent SC generation in chalcogenide W-type coaxial optical fiber, step-index tellurite fiber, and rib waveguide [17][18][19]. In the same year, Nguyen et al obtained mid-infrared SC with good coherence in cascaded tellurite and chalcogenide fibers [20].…”
Section: Introductionmentioning
confidence: 99%